Analysis of Buoyancy-Driven Flow in the Rocom Test Facility. (September 2017) - Feng, Qingqing; Bieder, Ulrich; Höhne, Thomas
Abstract: In emergency core cooling (ECC) situations after a loss of coolant accident, cold ECC water is injected into the hot water of the cold leg and downcomer. Temperature distributions near the wall and temperature gradients in time are important to be known for the assessment of thermal stresses. Numerous experiments were realized in the test facility ROCOM of the Helmholz Zentrum Dresden- Rossendorf, Dresden, Germany to investigate the effects of density differences between the primary loop inventory and the ECC water on the mixing in the downcomer. In 2005, an experiment with 5% flow rate in loop 1 and 10% density difference between ECC and loop water were compared to CFD calculations with Trio_U. In this paper, the same experiment is analyzed here with the TrioCFD code, taking into account 10 years of code and hardware development. The comparison of the LES to the experiment is globally satisfying. However, the calculation shows important turbulent fluctuations overestimating the measurements at the upper and lower downcomer sensors. Besides this, the resistance of the perforated drum seems to be under predicted. For further studies, a key issue seems to be an improved finer meshing of the perforated drum and of the wall near region of the downcomer.